Thermal energy grid storage using multi-junction photovoltaics. Issue 1 (6th December 2018) - Amy, Caleb; Seyf, Hamid Reza; Steiner, Myles A.; Friedman, Daniel J.; Henry, Asegun
Abstract : The storage of liquid silicon above 2000 °C and multi-junction photovoltaics enable affordable, geographically independent grid level energy storage. Abstract : As the cost of renewable energy falls below fossil fuels, the key barrier to widespread sustainable electricity has become availability on demand. Energy storage can enable renewables to provide this availability, but there is no clear technology that can meet the low cost needed. Thus, we introduce a concept termed thermal energy grid storage, which in this embodiment uses multi-junction photovoltaics as a heat engine. We report promising initial experimental results that suggest it is feasible and could meet the low cost required to reach full penetration of renewables. The approach exploits an important tradeoff between the realization of an extremely low cost per unit energy stored, by storing heat instead of electricity directly, and paying the penalty of a lower round trip efficiency. To understand why this tradeoff is advantageous, we first introduce a general framework for evaluating storage technologies that treats round trip efficiency, as well as cost per unit energy and power, as variables.